Gestión administrativa y su incidencia en la calidad del servicio de la pizzería “Pizzaditas" en la ciudad de Santo Domingo, año 2021 - Bazurto Marcillo, Monica Johana (2022)
The present investigation will be carried out where it will be analyzedthe administrative management that affects the quality of the service of the "PIZZADITAS" Pizzeria, where the problem isthe deficiency in the quality of the service, and in the management of personnel. Managers exercise an empirical administrative management, which affects the quality of service. TheAdministrative management must be implemented in companies to be able to plan, organize, direct and control the activities that are carried out, improve their performance and nurture their workers with knowledge through training on customer service, among others. The methodology to be used through quantitative research will be the surveys directed at the clients and workers of the company PIZZADITAS; while, through qualitative research, interviews with the owner will be carried out, which will allow collecting true information for the investigation.